2024
DOI: 10.3390/app14041561
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Incorporating Two Types of Dried Raspberry Pomace into Gluten-Free Bread on Its Nutritional and Antioxidant Characteristics

Anna Pecyna,
Monika Krzywicka,
Agata Blicharz-Kania
et al.

Abstract: The purpose of this study was to determine the impact of the pomace drying methods (freeze-drying and convection-drying) and their percentage (0–10%) on selected physicochemical properties of gluten-free bread. The contents of nutrients (protein, fiber, fat, ash, and carbohydrates), bioactive compounds, antioxidant properties, acidity, baking efficiency, and moisture of the obtained products were determined. Fortifying the bread with raspberry pomace resulted in a change in fiber content from 18.13% d. b. (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Therefore, they can be a valuable secondary raw material in the food industry due to their use in production, including innovative additives that enrich food products or as ingredients in dietary supplements [31]. Research has shown that raspberry pomace represents a valuable source of fiber and bioactive substances in gluten-free bread [32], waffles [33], and confectionery products [34]. Bobinaite et al [35] found that adding raspberry pomace extract to fruit purees resulted in an almost threefold increase in the total content of polyphenols, thus improving the functional properties of the products.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they can be a valuable secondary raw material in the food industry due to their use in production, including innovative additives that enrich food products or as ingredients in dietary supplements [31]. Research has shown that raspberry pomace represents a valuable source of fiber and bioactive substances in gluten-free bread [32], waffles [33], and confectionery products [34]. Bobinaite et al [35] found that adding raspberry pomace extract to fruit purees resulted in an almost threefold increase in the total content of polyphenols, thus improving the functional properties of the products.…”
Section: Introductionmentioning
confidence: 99%